2015
DOI: 10.3390/sports3030246
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Kinetics of Youth Baseball Catchers and Pitchers

Abstract: Abstract:The purpose of this study was to compare the throwing kinematics and kinetics of youth catchers and pitchers. It was hypothesized that catchers and pitchers would exhibit differences throughout the throwing motion. Descriptive statistics were used to investigate kinematics during the four events of throwing: foot contact (FC), maximum shoulder external rotation (MER), ball release (BR) and maximum shoulder internal rotation (MIR). Additionally, kinetics were investigated within phases of the events: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…When a runner attempts to steal second base, the catcher must complete the following actions in a short time: (1) quickly change the caught ball, (2) get up quickly, (3) step on the lead, and (4) throw with a small arm swing. Several studies have examined the mechanics of catchers throwing to second base, 17 but there are only a few studies on the throwing time to second base. Eto 8 reported that the throw to second base must be completed in about 2.0 s since a professional baseball player with fast sprinting velocity can run from first to second base in about 3.3–3.5 s, and the time from when the pitcher starts his pitching motion to when the catcher catches the pitch is about 1.3 s. Sakurai et al.…”
Section: Introductionmentioning
confidence: 99%
“…When a runner attempts to steal second base, the catcher must complete the following actions in a short time: (1) quickly change the caught ball, (2) get up quickly, (3) step on the lead, and (4) throw with a small arm swing. Several studies have examined the mechanics of catchers throwing to second base, 17 but there are only a few studies on the throwing time to second base. Eto 8 reported that the throw to second base must be completed in about 2.0 s since a professional baseball player with fast sprinting velocity can run from first to second base in about 3.3–3.5 s, and the time from when the pitcher starts his pitching motion to when the catcher catches the pitch is about 1.3 s. Sakurai et al.…”
Section: Introductionmentioning
confidence: 99%